Polymer modified asphalt composition and preparation method thereof
By using nano-scale inorganic materials, composite modifiers of plant polymerizable components and ionic liquids in asphalt materials, combined with one-step reaction and ultrasonic assisted synthesis technology, the problem of insufficient performance of traditional asphalt materials is solved, and high-temperature stability, low-temperature crack resistance, wear resistance and flexibility are improved, and environmentally friendly and sustainable.
Patent Information
- Application Number
- CN202411517815.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Traditional asphalt materials have limitations in high temperature stability, low temperature crack resistance, wear resistance and flexibility, which is difficult to meet the needs of modern complex traffic conditions, and the preparation process is complex and the environmental protection performance is poor.
The preparation method of polymer modified asphalt composition is adopted to improve the comprehensive performance of the asphalt composition by combining nano-scale inorganic materials, plant polymerizable components and ionic liquids, combined with one-step reaction and ultrasonic assisted synthesis technology.
It significantly improves the high-temperature stability, low-temperature crack resistance, wear resistance and flexibility of the asphalt composition, extends the service life of the road, and has the characteristics of environmental protection and sustainability, reducing environmental pollution.
Smart Images

Figure CN119039796B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of asphalt materials, in particular to a polymer modified asphalt composition and a preparation method thereof. Background Art
[0002] With the rapid development of transportation, the quality and performance requirements of roads are increasing day by day. Asphalt is a widely used material in road construction. The quality of its performance directly affects the service life and use effect of roads. Traditional asphalt materials have certain limitations in high temperature stability, low temperature crack resistance, wear resistance and flexibility, and it is difficult to meet the needs of complex modern traffic conditions. Under high temperature conditions, ordinary asphalt is easy to soften and deform, resulting in road rutting and other diseases, affecting the flatness and driving safety of roads. This is because the molecular structure of asphalt becomes loose at high temperatures and cannot withstand the repeated effects of vehicle loads. In low temperature environments, asphalt becomes brittle and hard, and cracks are easy to form, further reducing the durability of roads. In addition, the wear resistance of traditional asphalt is limited. On roads where vehicles travel frequently, the road surface is prone to wear, shortening the road maintenance cycle.
[0003] The existing technology has certain technical defects. First, most of the existing preparation methods use a single component to modify asphalt, which makes it difficult to achieve the synergistic effect of multiple components and cannot comprehensively improve the comprehensive performance of the asphalt composition in terms of structural stability, flexibility, anti-aging and other aspects. Secondly, the existing technology often relies on non-renewable chemical raw materials, and improperly handles organic solvents during use, and does not fully consider environmental protection and sustainable development concepts, causing great pressure on the environment. Moreover, the traditional process often has cumbersome and complicated steps, and does not adopt one-step reaction and ultrasonic-assisted synthesis technology, resulting in low production efficiency and difficulty in ensuring the stability of product quality. For this reason, we propose a polymer-modified asphalt composition and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a polymer modified asphalt composition and a preparation method thereof.
[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a method for preparing a polymer modified asphalt composition, the preparation method comprising the following specific steps:
[0006] Step 1: prepare a nano-scale inorganic material pretreatment product, select nano-silicon dioxide as the nano-scale inorganic material, heat it in a vacuum environment to remove impurities and moisture, and then cool it to room temperature;
[0007] Step 2, extracting the plant polymerizable components, using flax seeds as the plant raw material and crushing it, and then extracting it with an organic solvent. The extraction process is carried out in an extraction kettle with a stirring device to stir the extraction to ensure that the flax seeds are fully in contact with the organic solvent to obtain an extract, and then the extract is distilled through a rotary evaporator to remove the organic solvent to obtain a concentrated solution, and the concentrated solution is purified by silica gel column chromatography, using an eluent prepared by mixing ethanol and water in a volume ratio of 3:1-5:1 as the mobile phase, and the flow rate is 1ml / min-2ml / min, and the chromatography purification is carried out to obtain the purified plant polymerizable components;
[0008] Step 3, synthesizing and pretreating the ionic liquid, respectively dissolving the precursor substances containing the quaternary ammonium salt cation and the fluorine-containing organic anion in the organic solvent dichloromethane, slowly dropping the two solutions under the protection of an inert gas, stirring and reacting at room temperature after the dropwise addition is completed, removing the organic solvent by vacuum distillation after the reaction is completed, and obtaining the ionic liquid, and drying the ionic liquid to remove the residual moisture and organic solvent before using it;
[0009] Step 4, preparing a composite modifier, mixing the nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid in a solvent system of an organic solvent and water in a mass ratio of 1:2:3, placing the mixed solution in a reactor, and performing a one-step reaction under the conditions of a temperature of 60°C-80°C and a pressure of 1.5atm-2atm. During the reaction, using ultrasonic assisted synthesis technology, the ultrasonic frequency is maintained at 20kHz-40kHz, the stirring rate is 100r / min-200r / min, and the reaction time is 30min-60min to obtain a composite modifier;
[0010] Step 5, mixing the matrix asphalt and the composite modifier, the matrix asphalt is indirectly heated to 160°C-180°C with heat transfer oil in a heating kettle, the heating rate is 10°C / min-20°C / min, and the temperature is kept constant until no solid particles remain, the composite modifier is added to the heated matrix asphalt at a rate of 5g / min-10g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 20min-30min to make it evenly dispersed;
[0011] Step six, add the thermosensitive polymer and complete the preparation. First, prepare the thermosensitive polymer using the copolymer N-isopropylacrylamide containing poly (N-isopropylacrylamide) chain segment and other auxiliary monomers. Add the copolymer containing poly (N-isopropylacrylamide) chain segment as the thermosensitive polymer at a mass ratio of 1:5-1:10 between the thermosensitive polymer and the matrix asphalt. At the same time, stir alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 15min-25min to ensure uniform dispersion and no agglomeration. Then transfer the mixture to the shearing equipment for shearing to obtain the polymer modified asphalt composition.
[0012] As a further solution of the present invention: in the step 1, the nanoscale inorganic material is nano-silicon dioxide with a particle size of 10nm-50nm. The nano-silicon dioxide needs to be pretreated before use. The pretreatment process includes heating at 330℃-400℃ for 2h-3h in a vacuum environment to remove impurities and moisture adsorbed on the surface, and then cooling to room temperature under nitrogen protection.
[0013] As a further solution of the present invention: in the step 2, flax seeds are used as plant raw materials, which are crushed to a particle size of 0.1 mm-1 mm, and then extracted with n-hexane as an organic solvent, the mass ratio of flax seeds to n-hexane is 1:5-1:8, the extraction process is carried out in an extraction kettle with a stirring device, the stirring rate is 100 r / min-200 r / min, the extraction temperature is 40° C.-60° C., the extraction time is 2h-4h, and an extract is obtained. The extract is distilled on a rotary evaporator at 50° C.-70° C. and a vacuum degree of 0.08 MPa-0.1 MPa to remove the organic solvent and obtain a concentrated solution.
[0014] As a further scheme of the present invention: in the step three, the organic solvent is dichloromethane, and under the protection of argon, the two solutions are slowly added dropwise at -2°C-10°C, and the dropping speed is controlled at 0.5ml / min-1.5ml / min. After the dropwise addition is completed, the reaction is stirred at room temperature for 24h-48h. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid, which is dried before use and heated at 50°C-70°C under a vacuum environment for 3h-5h.
[0015] As a further scheme of the present invention: in the step six, the polymer chain segments of the thermosensitive polymer shrink at low temperatures and stretch at high temperatures, and the glass transition temperature is -20°C-20°C. The thermosensitive polymer is composed of a copolymer containing a poly(N-isopropylacrylamide) chain segment, and its synthesis process is as follows: a monomer containing a poly(N-isopropylacrylamide) chain segment and methyl acrylate and styrene as auxiliary monomers are polymerized in the presence of an initiator, the polymerization reaction temperature is 60°C-80°C, the polymerization reaction time is 4h-8h, the amount of initiator used is 0.5%-2% of the monomer mass, and stirring is continued during the polymerization reaction at a stirring rate of 100r / min-200r / min.
[0016] As a further scheme of the present invention: In step six, the base asphalt is pretreated before use, and the pretreatment process includes heating at 120℃-140℃ for 2h-3h to remove moisture and light volatiles, and then cooling to room temperature under nitrogen protection.
[0017] As a further scheme of the present invention: in the step 4, the solvent system is an organic solvent toluene and water mixed in a volume ratio of 2:1. Before using the solvent system, the toluene is pretreated, and the pretreatment process includes stirring at room temperature for 1h-2h in the presence of concentrated sulfuric acid, then washing with distilled water until neutral, and then drying with anhydrous sodium sulfate, and finally filtering to remove sodium sulfate under nitrogen protection to obtain pretreated toluene.
[0018] As a further solution of the present invention: in the step four, the ultrasonic generating device in the ultrasonic-assisted synthesis technology is a piezoelectric ultrasonic generator with a power of 200W-500W. When using the ultrasonic generating device, the ultrasonic probe needs to be immersed in the solution in the reactor with an immersion depth of 2cm-3cm to ensure that the ultrasonic wave can effectively act on the reaction system.
[0019] As a further solution of the present invention: in the step six, the shearing time ranges from 1h to 2h, the shearing head speed is 3000r / min to 5000r / min, and the shearing temperature is 140°C to 160°C.
[0020] In addition, the present invention also provides a polymer modified asphalt composition, and the polymer modified asphalt composition is prepared by the preparation method of the polymer modified asphalt composition.
[0021] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0022] 1. The present invention improves the performance of the asphalt composition through composite modification of multiple components. Nano-silicon dioxide enhances surface activity after pretreatment, fills the gaps in asphalt molecules, and improves structural stability and wear resistance. Because of its nano size, it is tightly combined with asphalt molecules. After a series of treatments, the plant polymerizable components extracted from flax seeds react with asphalt molecules by their active groups to improve flexibility and adhesion. Ionic liquids are synthesized and pretreated, in which anions and cations interact with the active sites of asphalt molecules to improve anti-aging performance. The thermosensitive polymer is composed of a copolymer containing specific chain segments. Low-temperature shrinkage makes the molecular structure tight and crack-resistant, and high-temperature stretching adapts to volume expansion and remains stable, effectively improving high-temperature stability and low-temperature crack resistance, and extending the service life of the paved material.
[0023] 2. The present invention has significant environmental advantages by selecting flax seeds as the raw material of plant polymerizable components. Flax seeds are a natural and renewable resource, which is in sharp contrast to traditional chemical raw materials. Flax seeds can absorb carbon dioxide during their growth and have a positive impact on the environment. Although organic solvents are used when extracting plant polymerizable components, these organic solvents have been reasonably treated to reduce pollution to the environment. The n-hexane used in the extraction process is removed by distillation through a rotary evaporator after the extraction task is completed, thereby avoiding the waste of organic solvents and potential harm to the environment. The dichloromethane used in the synthesis process of the ionic liquid is also removed by reduced pressure distillation after the reaction is completed, further protecting the environment, complying with the concept of sustainable development, and providing a feasible path for the green development of the asphalt industry.
[0024] 3. The present invention prepares the composite modifier by adopting a one-step reaction and combining it with ultrasonic-assisted synthesis technology. The one-step reaction reduces the reaction steps and improves production efficiency. Compared with the traditional multi-step process, it reduces the production time and equipment requirements. When preparing the composite modifier, the nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid are mixed in a pretreated solvent system at a specific mass ratio, and the reaction is carried out under specific temperature and high pressure conditions. In the ultrasonic-assisted synthesis technology, the piezoelectric ultrasonic generator makes the reaction more complete and uniform, better controls the reaction process and product quality, and carries out detailed specifications for the pretreatment process of the matrix asphalt and the solvent, further optimizes the entire preparation process, and improves the stability of the product quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A schematic diagram of the method steps in an embodiment of the present invention;
[0026] Figure 2 This is a schematic diagram of performance test results in an embodiment of the present invention;
[0027] Figure 3This is a schematic diagram of the test results of environmental indicators in an embodiment of the present invention;
[0028] Figure 4 Schematic diagram of production efficiency test results in an embodiment of the present invention. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0030] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] Please see attached Figure 1 -Attached Figure 4 The preparation method of the polymer modified asphalt composition of the present invention comprises the following specific steps:
[0032] Step 1: prepare a nano-scale inorganic material pretreatment product, select nano-silicon dioxide as the nano-scale inorganic material, heat it in a vacuum environment to remove impurities and moisture, and then cool it to room temperature;
[0033] Step 2, extracting the plant polymerizable components, using flax seeds as the plant raw material and crushing it, and then extracting it with an organic solvent. The extraction process is carried out in an extraction kettle with a stirring device to stir the extraction to ensure that the flax seeds are fully in contact with the organic solvent to obtain an extract, and then the extract is distilled through a rotary evaporator to remove the organic solvent to obtain a concentrated solution, and the concentrated solution is purified by silica gel column chromatography, using an eluent prepared by mixing ethanol and water in a volume ratio of 3:1-5:1 as the mobile phase, and the flow rate is 1ml / min-2ml / min, and the chromatography purification is carried out to obtain the purified plant polymerizable components;
[0034] Step 3, synthesizing and pretreating the ionic liquid, respectively dissolving the precursor substances containing the quaternary ammonium salt cation and the fluorine-containing organic anion in the organic solvent dichloromethane, slowly dropping the two solutions under the protection of an inert gas, stirring and reacting at room temperature after the dropwise addition is completed, removing the organic solvent by vacuum distillation after the reaction is completed, and obtaining the ionic liquid, and drying the ionic liquid to remove the residual moisture and organic solvent before using it;
[0035] Step 4, preparing a composite modifier, mixing the nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid in a solvent system of an organic solvent and water in a mass ratio of 1:2:3, placing the mixed solution in a reactor, and performing a one-step reaction under the conditions of a temperature of 60°C-80°C and a pressure of 1.5atm-2atm. During the reaction, using ultrasonic assisted synthesis technology, the ultrasonic frequency is maintained at 20kHz-40kHz, the stirring rate is 100r / min-200r / min, and the reaction time is 30min-60min to obtain a composite modifier;
[0036] Step 5, mixing the matrix asphalt and the composite modifier, the matrix asphalt is indirectly heated to 160°C-180°C with heat transfer oil in a heating kettle, the heating rate is 10°C / min-20°C / min, and the temperature is kept constant until no solid particles remain, the composite modifier is added to the heated matrix asphalt at a rate of 5g / min-10g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 20min-30min to make it evenly dispersed;
[0037] Step six, add the thermosensitive polymer and complete the preparation. First, prepare the thermosensitive polymer using the copolymer N-isopropylacrylamide containing poly (N-isopropylacrylamide) chain segment and other auxiliary monomers. Add the copolymer containing poly (N-isopropylacrylamide) chain segment as the thermosensitive polymer at a mass ratio of 1:5-1:10 between the thermosensitive polymer and the matrix asphalt. At the same time, stir alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 15min-25min to ensure uniform dispersion and no agglomeration. Then transfer the mixture to the shearing equipment for shearing to obtain the polymer modified asphalt composition.
[0038] In one embodiment of the present invention: in step one, the nanoscale inorganic material is nano-silicon dioxide with a particle size of 10nm-50nm. The nano-silicon dioxide needs to be pretreated before use. The pretreatment process includes heating at 330℃-400℃ for 2h-3h in a vacuum environment to remove impurities and moisture adsorbed on the surface, and then cooling to room temperature under nitrogen protection.
[0039] In one embodiment of the present invention: in step 2, flax seeds are used as plant raw materials, which are crushed to a particle size of 0.1 mm-1 mm, and then extracted with n-hexane as an organic solvent, the mass ratio of flax seeds to n-hexane is 1:5-1:8, the extraction process is carried out in an extraction kettle with a stirring device, the stirring rate is 100 r / min-200 r / min, the extraction temperature is 40° C.-60° C., the extraction time is 2h-4h, and an extract is obtained. The extract is distilled on a rotary evaporator at 50° C.-70° C. and a vacuum degree of 0.08 MPa-0.1 MPa to remove the organic solvent and obtain a concentrated solution.
[0040] In one embodiment of the present invention: in step three, the organic solvent is dichloromethane, and under the protection of argon, the two solutions are slowly added dropwise at -2°C-10°C, and the dropping speed is controlled at 0.5ml / min-1.5ml / min. After the dropwise addition is completed, the reaction is stirred at room temperature for 24h-48h. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid, which is dried before use and heated at 50°C-70°C under a vacuum environment for 3h-5h.
[0041] In one embodiment of the present invention: in step six, the polymer chain segments of the thermosensitive polymer shrink at low temperatures and stretch at high temperatures, and the glass transition temperature is -20°C-20°C. The thermosensitive polymer is composed of a copolymer containing a poly(N-isopropylacrylamide) chain segment, and its synthesis process is as follows: a monomer containing a poly(N-isopropylacrylamide) chain segment and methyl acrylate and styrene as auxiliary monomers are polymerized in the presence of an initiator, the polymerization reaction temperature is 60°C-80°C, the polymerization reaction time is 4h-8h, the amount of initiator used is 0.5%-2% of the monomer mass, and stirring is continued during the polymerization reaction at a stirring rate of 100r / min-200r / min.
[0042] In one embodiment of the present invention: In step six, the base asphalt is pretreated before use, and the pretreatment process includes heating at 120°C-140°C for 2h-3h to remove moisture and light volatiles, and then cooling to room temperature under nitrogen protection.
[0043] In one embodiment of the present invention: in step 4, the solvent system is an organic solvent of toluene and water mixed in a volume ratio of 2:1. Before using the solvent system, the toluene is pretreated, and the pretreatment process includes stirring at room temperature for 1h-2h in the presence of concentrated sulfuric acid, then washing with distilled water until neutral, and then drying with anhydrous sodium sulfate, and finally filtering under nitrogen protection to remove sodium sulfate to obtain pretreated toluene.
[0044] In one embodiment of the present invention: In step four, the ultrasonic generating device in the ultrasonic-assisted synthesis technology is a piezoelectric ultrasonic generator with a power of 200W-500W. When using the ultrasonic generating device, the ultrasonic probe needs to be immersed in the solution in the reactor with an immersion depth of 2cm-3cm to ensure that the ultrasonic wave can effectively act on the reaction system.
[0045] In one embodiment of the present invention: in step six, the shearing time ranges from 1h to 2h, the shearing head speed is 3000r / min to 5000r / min, and the shearing temperature is 140°C to 160°C.
[0046] Example 1, please refer to the attached Figure 1 -Attached Figure 4First, nano-silicon dioxide with a particle size of 10nm-50nm was selected as the nano-scale inorganic material, and was heated at 400℃ for 3h under a vacuum environment to remove impurities and moisture, and then cooled to room temperature under nitrogen protection. Flax seeds were used as plant raw materials, crushed to a particle size of 1mm, and extracted with n-hexane (the mass ratio of flax seeds to n-hexane was 1:8) at 60℃ and a stirring rate of 200r / min for 4h to obtain an extract. The extract was distilled on a rotary evaporator at 70℃ and a vacuum degree of 0.1MPa to remove the organic solvent to obtain a concentrate, and then purified by silica gel column chromatography (using an eluent prepared by mixing ethanol and water in a volume ratio of 5:1 as the mobile phase, and a flow rate of 2ml / min) to obtain a plant polymerizable component, and the quaternary ammonium salt-containing The precursors of cations and fluorine-containing organic anions are dissolved in an organic solvent, dichloromethane, respectively. Under argon protection, the two solutions are slowly added dropwise at 8°C (the dropping speed is controlled at 1.5 ml / min). After the addition is completed, the reaction is stirred at room temperature for 48 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid. Before use, it is heated at 70°C for 5 hours under a vacuum environment for drying. The nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid are mixed in a solvent system in which toluene and water are mixed in a volume ratio of 2:1 at a mass ratio of 1:2:3. The mixed solution is placed in a reactor and a one-step reaction is carried out at a temperature of 80°C and a pressure of 2atm. During the reaction, A piezoelectric ultrasonic generator (power of 500 W, probe immersion depth of 3 cm) was used to assist the synthesis, and the ultrasonic frequency was maintained at 40 kHz, the stirring rate was 200 r / min, and the reaction time was 60 min to obtain a composite modifier. The matrix asphalt was heated at 140 ° C for 3 h to remove moisture and light volatiles, and then cooled to room temperature under nitrogen protection. Then, it was indirectly heated to 180 ° C in a heating kettle with heat transfer oil, and the heating rate was 20 ° C / min. The temperature was kept constant until no solid particles remained. The composite modifier was added to the heated matrix asphalt at a rate of 10 g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 800 r / min for 30 min to make it uniformly dispersed. The matrix asphalt was heated at 140 ° C for 3 h to remove moisture and light volatiles, and then cooled to room temperature under nitrogen protection. Then, it was indirectly heated to 180 ° C in a heating kettle with heat transfer oil, and the heating rate was 20 ° C / min. The temperature was kept constant until no solid particles remained. The composite modifier was added to the heated matrix asphalt at a rate of 10 g / min. At the same time, it was stirred alternately clockwise and counterclockwise at a stirring rate of 800 r / min for 30 min to make it uniformly dispersed. A thermosensitive polymer is prepared by polymerizing a 2-propyl acrylamide) chain segment and methyl acrylate and styrene as auxiliary monomers in the presence of an initiator (polymerization temperature is 80°C, polymerization time is 8h, the amount of initiator is 2% of the mass of the monomer, stirring is continued during the polymerization reaction, and the stirring rate is 200r / min). The thermosensitive polymer is added at a mass ratio of thermosensitive polymer to matrix asphalt of 1:10. At the same time, the mixture is stirred alternately clockwise and counterclockwise at a stirring rate of 800r / min for 25min to ensure uniform dispersion without agglomeration. The mixture is then transferred to a shearing device and sheared for 2h at a shear head speed of 3000r / min and a temperature of 140°C-160°C to obtain a polymer modified asphalt composition.
[0047] Example 2, please refer to the attached Figure 1 -Attached Figure 4First, nano-silicon dioxide with a particle size of 10nm-50nm was selected as the nano-scale inorganic material, and was heated at 400℃ for 2h under a vacuum environment to remove impurities and moisture, and then cooled to room temperature under nitrogen protection. Flax seeds were used as plant raw materials, crushed to a particle size of 1mm, and extracted with n-hexane (the mass ratio of flax seeds to n-hexane was 1:5) at 40℃ and a stirring rate of 100r / min for 2h to obtain an extract. The extract was distilled on a rotary evaporator at 50℃ and a vacuum degree of 0.08MPa to remove the organic solvent to obtain a concentrate, and then purified by silica gel column chromatography (using an eluent prepared by mixing ethanol and water in a volume ratio of 3:1 as the mobile phase, and a flow rate of 1ml / min) to obtain a plant polymerizable component, and the quaternary ammonium salt-containing The precursors of cations and fluorine-containing organic anions are dissolved in an organic solvent, dichloromethane, respectively. Under the protection of argon, the two solutions are slowly added dropwise at -2°C (the dropping speed is controlled at 0.5 ml / min). After the addition is completed, the reaction is stirred at room temperature for 24 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid. Before use, it is dried by heating at 50°C for 3 hours under a vacuum environment. The nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid are mixed in a solvent system in which toluene and water are mixed in a volume ratio of 2:1 at a mass ratio of 1:2:3. The mixed solution is placed in a reactor and a one-step reaction is carried out at a temperature of 60°C and a pressure of 1.5 atm. During the reaction process, In the process, a piezoelectric ultrasonic generator (power of 200 W, probe immersion depth of 2 cm) was used to assist the synthesis, and the ultrasonic frequency was maintained at 20 kHz, the stirring rate was 100 r / min, and the reaction time was 30 min to obtain a composite modifier. The matrix asphalt was heated at 120 ° C for 2 h to remove the moisture and light volatiles therein, and then cooled to room temperature under nitrogen protection, and then indirectly heated to 160 ° C in a heating kettle with heat transfer oil, the heating rate was 10 ° C / min, and the temperature was kept constant until no solid particles remained. The composite modifier was added to the heated matrix asphalt at a rate of 5 g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 500 r / min for 20 min to make it uniformly dispersed ... A thermosensitive polymer is prepared by polymerizing a 2-propyl acrylamide) chain segment and methyl acrylate and styrene as auxiliary monomers in the presence of an initiator (polymerization temperature is 60°C, polymerization time is 4h, initiator dosage is 0.5% of monomer mass, stirring is continued during the polymerization reaction, and stirring rate is 100r / min). The thermosensitive polymer is added at a mass ratio of thermosensitive polymer to matrix asphalt of 1:5. At the same time, stirring is alternately carried out clockwise and counterclockwise at a stirring rate of 500r / min for 15min to ensure uniform dispersion without agglomeration. The mixture is then transferred to a shearing device and sheared for 2h at a shear head speed of 5000r / min and a temperature of 160°C-160°C to obtain a polymer modified asphalt composition.
[0048] Example 3, please refer to the attached Figure 1 -Attached Figure 4First, nano zinc oxide with a particle size of 10nm-50nm was selected as the nano-scale inorganic material, and was heated at 330℃ for 2h in a vacuum environment to remove impurities and moisture, and then cooled to room temperature under argon protection. Palm oil residue was used as the plant raw material, crushed to a particle size of 1mm, and extracted with petroleum ether (the mass ratio of walnut shell to petroleum ether was 1:8) at 60℃ and a stirring rate of 200r / min for 4h to obtain an extract. The extract was distilled on a rotary evaporator at 70℃ and a vacuum degree of 0.1MPa to remove the organic solvent to obtain a concentrate, and then purified by silica gel column chromatography (using an eluent prepared by mixing ethanol and water in a volume ratio of 5:1 as the mobile phase, and a flow rate of 2ml / min) to obtain the plant polymerizable component, and the imidazole-containing The precursors of salt cations and chlorine-containing organic anions are dissolved in the organic solvent chloroform respectively. Under nitrogen protection, the two solutions are slowly added dropwise at 8°C (the dropping speed is controlled at 1.5 ml / min). After the addition is completed, the reaction is stirred at room temperature for 48 hours. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid, which is heated at 70°C for 5 hours under a vacuum environment for drying before use. The nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid are mixed in a solvent system in which xylene and water are mixed in a volume ratio of 2:1 at a mass ratio of 1:2:3. The mixed solution is placed in a reactor and a one-step reaction is carried out at a temperature of 80°C and a pressure of 2atm. During the reaction process In the process, a piezoelectric ultrasonic generator (power of 500 W, probe immersion depth of 3 cm) was used to assist the synthesis, and the ultrasonic frequency was maintained at 40 kHz, the stirring rate was 200 r / min, and the reaction time was 60 min to obtain a composite modifier. The matrix asphalt was heated at 140 ° C for 3 h to remove the moisture and light volatiles therein, and then cooled to room temperature under argon protection, and then indirectly heated to 180 ° C in a heating kettle with heat transfer oil, the heating rate was 20 ° C / min, and the temperature was kept constant until no solid particles remained. The composite modifier was added to the heated matrix asphalt at a rate of 8 g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 800 r / min for 30 min to make it uniformly dispersed ... Thermosensitive polymer was prepared by polymerization of ethyl acrylate, acrylonitrile and N-isopropylacrylamide) chain segments and ethyl acrylate and acrylonitrile as auxiliary monomers in the presence of an initiator (polymerization temperature was 80°C, polymerization time was 6h, initiator amount was 2% of monomer mass, stirring was continued during the polymerization reaction, and stirring rate was 200r / min). Thermosensitive polymer was added at a mass ratio of 1:10 between the thermosensitive polymer and the matrix asphalt. The mixture was stirred alternately clockwise and counterclockwise at a stirring rate of 800r / min for 25min to ensure uniform dispersion without agglomeration. The mixture was then transferred to a shearing device and sheared for 2h at a shear head speed of 3000r / min and a temperature of 140°C to obtain a polymer modified asphalt composition.
[0049] Comparative Example 1
[0050] The polymer modified asphalt provided in the patent document entitled "Polymer modified asphalt and preparation method thereof" with application publication number CN112029304B is prepared by using the following raw materials in accordance with the following steps:
[0051] A. Preparation of composite modifier:
[0052] 30g of amino-terminated hyperbranched polyamide HyperN10 and 10g of ethylenediaminetetraacetic acid were mixed and put into a stirring reaction pot, the stirrer was started, the temperature was raised to 130°C, the heating temperature was controlled to be 140°C, and then 4g of diethanolamine was slowly added at a rate of 1kg / min, and stirred at a temperature of 140°C for 30min, and 17g of dibutyl phthalate and 32g of diisodecyl adipate were added, and stirred for another 30min to obtain a composite modifier;
[0053] B. Preparation of polymer modified asphalt:
[0054] Put 500g70# petroleum asphalt into a mixing pot, heat to 180℃, add 25gSBS and 30g of the composite modifier prepared in step A, start the mixer to stir, after the polymer swells for 30min, use a shearing machine to shear the modified asphalt for 2h at a shear rate of 4000r / min, and then develop for 5h to obtain.
[0055] Comparative Example 2
[0056] A polymer modified asphalt provided in the patent document entitled "Polymer modified asphalt and preparation method" with application publication number CN101531817B is prepared by using the following raw materials in accordance with the following steps:
[0057] It is composed of the following raw materials in percentage by weight:
[0058] Base asphalt: 85-96%;
[0059] Maleic anhydride grafted ethylene-vinyl acetate copolymer (EVA): 2-8%;
[0060] Styrene butadiene rubber (SBR): 1-5%;
[0061] Tackifier: 0.5-2%;
[0062] The grafting rate of maleic anhydride grafted ethylene-vinyl acetate copolymer (M-EVA) is 1-5%, styrene-butadiene rubber (SBR) is in powder form, and the tackifier is polyvinyl chloride resin (PVCSG-5), or phenolic resin (2124), or natural asphalt produced in Xinjiang;
[0063] Heat the base asphalt until it is completely blended, add the grafted modified ethylene-vinyl acetate copolymer (M-EVA), continue heating to stabilize its temperature within the range of 150-190°C, and perform high-speed shearing for 30-60 minutes at a rotation speed of 2000-4000 rpm to achieve high-temperature shear blending to obtain the product.
[0064] Design of the experiment:
[0065] Experimental materials and equipment:
[0066] Materials: various raw materials required for Example 1, Example 2, Comparative Example 1 and Comparative Example 2, including nano-silicon dioxide, nano-zinc oxide, linseed, palm oil residue, various organic solvents, ionic liquid precursors, matrix asphalt, auxiliary monomers, etc.;
[0067] Equipment: vacuum heating equipment, pulverizer, extraction kettle, rotary evaporator, silica gel column chromatography device, reaction kettle, ultrasonic generator, heating kettle, shearing equipment, mixer, thermometer, pressure gauge;
[0068] Experimental steps:
[0069] Polymer modified asphalt compositions were prepared according to the preparation methods of Example 1, Example 2, Comparative Example 1 and Comparative Example 2, respectively.
[0070] Performance Test:
[0071] High temperature stability test: The softening point is determined by the ring and ball method. The asphalt sample is heated at a specified heating rate. The temperature when the steel ball passes through the asphalt sample and sinks to a certain position is the softening point. The higher the softening point, the better the stability of the asphalt at high temperatures.
[0072] Low temperature crack resistance test:
[0073] In the low-temperature ductility test, the asphalt sample is made into a specimen of a specified size. The specimen is stretched at a specified tensile rate in a low-temperature environment (20°C) and the elongation length when the specimen breaks is measured, i.e. the ductility. The larger the ductility, the better the crack resistance of the asphalt at low temperatures.
[0074] Wear resistance test
[0075] The abrasion test uses a specific abrasion equipment, the Los Angeles abrasion tester, to make the asphalt sample into a specimen of a specified size. Under certain rotation speed and loading conditions, the specimen is brought into contact with the abrasive in step 1 and worn for a certain period of time. The mass loss of the specimen before and after wear, i.e., the wear loss, is measured. The smaller the wear loss, the stronger the wear resistance of the asphalt.
[0076] Flexibility test
[0077] The bending test is used to make the asphalt sample into a specimen of specified size. The specimen is bent at a specified bending radius and bending angle. The deformation of the specimen during the bending process is observed and the maximum deformation of the specimen surface is measured. The smaller the deformation, the better the flexibility of the asphalt.
[0078] Adhesion test
[0079] In the pull-out test, the asphalt sample is smeared on the specified base material to make a test piece of specified size. At a specified tensile rate, the test piece is pulled off the base material using a pulling device, and the maximum pull-out force during the pulling process is measured. The greater the pull-out force, the better the adhesion between the asphalt and the base material.
[0080] Anti-aging performance test
[0081] An accelerated aging test is conducted by placing asphalt samples in an accelerated aging device to simulate aging factors in the actual environment, including high temperature, ultraviolet radiation, and oxidation. After a certain period of aging treatment (100 hours), the change rate of various performance indicators (softening point, elongation) of the asphalt samples is measured. The smaller the change rate, the better the asphalt's anti-aging performance.
[0082] Environmental index test
[0083] Detect organic solvent residues and waste gas emissions, evaluate the sustainability of plant raw materials, use gas chromatography to detect organic solvent residues, and measure the content of harmful substances in waste gas emissions through testing equipment;
[0084] Exhaust emission classification: Classification based on the total content of harmful substances (volatile organic compounds VOCs, sulfur dioxide SO2, nitrogen oxides NOx) in the exhaust gas;
[0085] Class A: The total content of harmful substances is less than 10mg / m³;
[0086] Class B: The total content of harmful substances is between 10mg / m³-50mg / m³;
[0087] Class C: The total content of harmful substances is higher than 50mg / m³;
[0088] Production efficiency test
[0089] Record the preparation time, count the number and type of equipment needed, record the total time from raw material preparation to the final product, and count the number and type of various equipment used in the preparation process.
[0090] By the attached Figure 2 -Attached Figure 4The results show that it can be clearly seen that Example 1 is superior to Example 2, Comparative Example 1 and Comparative Example 2 in terms of performance improvement, environmental advantages and production efficiency.
[0091] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A method for preparing a polymer modified asphalt composition, characterized in that: The preparation method comprises the following specific steps: Step 1: prepare a nano-scale inorganic material pretreatment product, select nano-silicon dioxide as the nano-scale inorganic material, heat it in a vacuum environment to remove impurities and moisture, and then cool it to room temperature; Step 2: extracting the plant polymerizable components, using flax seeds as the plant raw material and crushing them, and then extracting them with an organic solvent. The extraction process is carried out in an extraction kettle with a stirring device to obtain an extract, and then the extract is distilled through a rotary evaporator to remove the organic solvent to obtain a concentrated solution. The concentrated solution is purified by silica gel column chromatography, using an eluent prepared by mixing ethanol and water in a volume ratio of 3:1-5:1 as the mobile phase, and the flow rate is 1 ml / min-2 ml / min, and the purified plant polymerizable components are obtained; Step 3, synthesizing and pretreating the ionic liquid, respectively dissolving the precursor substances containing the quaternary ammonium salt cation and the fluorine-containing organic anion in the organic solvent dichloromethane, slowly dropping the two solutions under the protection of an inert gas, stirring and reacting at room temperature after the dropwise addition is completed, removing the organic solvent by vacuum distillation after the reaction is completed, and obtaining the ionic liquid, and drying the ionic liquid to remove the residual moisture and organic solvent before using it; Step 4, preparing a composite modifier, mixing the nano-scale inorganic material pretreatment, the plant polymerizable component and the pretreated ionic liquid in a solvent system of an organic solvent and water in a mass ratio of 1:2:3, placing the mixed solution in a reactor, and performing a one-step reaction under the conditions of a temperature of 60°C-80°C and a pressure of 1.5atm-2atm. During the reaction, using ultrasonic assisted synthesis technology, the ultrasonic frequency is maintained at 20kHz-40kHz, the stirring rate is 100r / min-200r / min, and the reaction time is 30min-60min to obtain a composite modifier; Step 5, mixing the matrix asphalt and the composite modifier, the matrix asphalt is indirectly heated to 160°C-180°C in a heating kettle with heat transfer oil, the heating rate is 10°C / min-20°C / min, and the temperature is kept constant until no solid particles remain, the composite modifier is added to the heated matrix asphalt at a rate of 5g / min-10g / min, and stirred alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 20min-30min to make it evenly dispersed; Step six, add the thermosensitive polymer and complete the preparation. First, prepare the thermosensitive polymer using the monomer containing the poly N-isopropylacrylamide chain segment and other auxiliary monomers. Add the monomer containing the poly N-isopropylacrylamide chain segment as the thermosensitive polymer at a mass ratio of 1:5-1:10 between the thermosensitive polymer and the matrix asphalt. At the same time, stir alternately clockwise and counterclockwise at a stirring rate of 500r / min-800r / min for 15min-25min to ensure uniform dispersion and no agglomeration. Then transfer the mixture to the shearing equipment for shearing to obtain the polymer modified asphalt composition.
2. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step 1, the nanoscale inorganic material is nano-silicon dioxide with a particle size of 10nm-50nm. The nano-silicon dioxide needs to be pretreated before use. The pretreatment process includes heating at 330℃-400℃ for 2h-3h in a vacuum environment to remove impurities and moisture adsorbed on the surface, and then cooling to room temperature under nitrogen protection.
3. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step 2, flax seeds are used as plant raw materials, crushed to a particle size of 0.1 mm-1 mm, and then extracted with n-hexane as an organic solvent, the mass ratio of flax seeds to n-hexane is 1:5-1:8, the extraction process is carried out in an extraction kettle with a stirring device, the stirring rate is 100 r / min-200 r / min, the extraction temperature is 40° C.-60° C., the extraction time is 2 h-4 h, and an extract is obtained. The extract is distilled on a rotary evaporator at 50° C.-70° C. and a vacuum degree of 0.08 MPa-0.1 MPa to remove the organic solvent and obtain a concentrated solution.
4. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step 3, the organic solvent is dichloromethane, and under the protection of argon, the two solutions are slowly added dropwise at -2°C-10°C, and the dropping speed is controlled at 0.5ml / min-1.5ml / min. After the addition is completed, the reaction is stirred at room temperature for 24h-48h. After the reaction is completed, the organic solvent is removed by reduced pressure distillation to obtain an ionic liquid, which is dried before use and heated at 50°C-70°C under a vacuum environment for 3h-5h.
5. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step six, the polymer chain segments of the thermosensitive polymer shrink at low temperatures and stretch at high temperatures, and the glass transition temperature is -20°C-20°C. The thermosensitive polymer is composed of a copolymer of monomers containing poly N-isopropylacrylamide chain segments, and its synthesis process is as follows: the monomers containing poly N-isopropylacrylamide chain segments and methyl acrylate and styrene as auxiliary monomers are polymerized in the presence of an initiator, the polymerization reaction temperature is 60°C-80°C, the polymerization reaction time is 4h-8h, the amount of initiator used is 0.5%-2% of the monomer mass, and stirring is continued during the polymerization reaction, and the stirring rate is 100r / min-200r / min.
6. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step six, the base asphalt is pretreated before use, and the pretreatment process includes heating at 120°C-140°C for 2h-3h to remove moisture and light volatiles, and then cooling to room temperature under nitrogen protection.
7. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step 4, the solvent system is an organic solvent of toluene and water mixed in a volume ratio of 2:
1. Before using the solvent system, the toluene is pretreated, and the pretreatment process includes stirring at room temperature for 1h-2h in the presence of concentrated sulfuric acid, then washing with distilled water until neutral, and then drying with anhydrous sodium sulfate, and finally filtering under nitrogen protection to remove sodium sulfate to obtain pretreated toluene.
8. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step 4, the ultrasonic generating device in the ultrasonic-assisted synthesis technology is a piezoelectric ultrasonic generator with a power of 200W-500W. When using the ultrasonic generating device, the ultrasonic probe needs to be immersed in the solution in the reactor with an immersion depth of 2cm-3cm to ensure that the ultrasonic wave can effectively act on the reaction system.
9. The method for preparing the polymer modified asphalt composition according to claim 1, characterized in that: In the step six, the shearing time ranges from 1 h to 2 h, the shearing head speed is 3000 r / min to 5000 r / min, and the shearing temperature is 140° C. to 160° C.
10. A polymer modified asphalt composition suitable for the preparation method of the polymer modified asphalt composition according to any one of claims 1 to 9, characterized in that: The polymer modified asphalt composition is prepared by a preparation method of a polymer modified asphalt composition.
Citation Information
Patent Citations
Polymer modified asphalt and preparation method thereof
CN101531817B
Polymer-modified asphalt and its preparation method
CN112029304B
Warm-mixed rubber asphalt and preparation method thereof
CN106810888A
Porous carbon polymer / block copolymer modified asphalt as well as preparation method and application thereof
CN116285400A